Enhancing English and accounting skills through a VOCABING-based technology program for MSMEs in Kediri - Angga Prasongko; Eni Srihastuti (Universitas Muhammadiyah Malang, 2024)
Digital economic transformation which is the impact of technological development changes the perspective of Indonesian on economic behavior. The use of technology in economics activity is increasing nowadays. It impacts on the development of the economic sectors. Macro, Small and Medium Enterprises (MSME) one of the business roles in Indonesia have to do some innovation for its existing in today's trading world. The strategy that can be implemented for facing that case is by adapting the technology use and enhancing the quality of human resources through increasing competence and skills. Considering that the performance of an organization is determined by the human resources it has. Community service program through Integrated Training; Vocabulary Building & Accounting (VOCABING)-Based Technology needs to be held for MSMEs in Kediri. These activities include training in English and the Use of Accounting Technology for improving MSMEs skill. it is based on vocabulary mastery which influence the ability to understand the complex information and instructions. The activity held two days series through four steps; planning, implementation, evaluations, and reporting. For proving the training’s goals, it used tests and assessment. The results showed that there was an increase of 12.5% in the final English test score and participants completed the work instruction assessment correctly.